Kepemilikan Manajerial, Kepemilikan Institusional dan Kebijakan Dividen serta Free Cash Flow sebagai Pemoderasi - Dewi, Ni Made Ari Trisna; Widanaputra, Anak Agung Gde Putu (E-Jurnal Akuntansi, 2021)
This study aims to determine the effect of managerial ownership and institutional ownership on dividend policy with free cash flow as a moderating variable. This research was conducted at manufacturing companies listed on the Indonesia Stock Exchange (BEI) in 2015-2019. The sample was selected by means of a purposive sampling method with 42 companies as samples and 210 observations. The analysis technique used in this research is Moderated Regression Analysis (MRA). The results of this study indicate that the higher the managerial ownership, the higher the dividend policy, especially in companies that have high free cash flow, and the higher the institutional ownership, the higher the dividend policy, especially in companies with high free cash flow. Keywords: Managerial Ownership; Institutional Ownership; Free Cash Flow; Dividend Policy.